ICTs and Development, What is Missing? - Sascha Rosenberger (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2014)
A review of literature indicates that most approaches emphasize bridging the digital divide, an approach focused solely on material gaps. However, the digital divide is perhaps the last of many, preceded by social, educational, economic, knowledge, and motivational divides. This stems from an incomplete assessment of the underlying characteristics of Information and Communication Technologies for Development (ICT4D), which helps to perpetuate positivist approaches to technology deployment between social groups inside countries, as well as between countries. ICT4D is therefore seen as a misnomer that puts undue pressure on developing countries and neglects the responsibilities of actors in developed countries. The application of the notions of freedom, as presented by Sen and Stallman, in the analysis of ICT4D prompts for a more thorough consideration of the characteristics of technology being pushed for use in developing countries. This leads to the conclusion that common ICT4D approaches could reinforce developing countriess' dependence on foreign actors and delay or entirely prevent the development of locally relevant and empowering solutions.
Keywords: 330; ICT4D; Free software; Development as freedom; Informationstechnik; Entwicklung; Digitale Spaltung; Freiheit; Entwicklungsländer